An in vivo and in vitro toxicological characterisation of realistic nanoscale CeO2 inhalation exposures. Issue 8 (December 2012) - Demokritou, Philip; Gass, Samuel; Pyrgiotakis, Georgios; Cohen, Joel M.; Goldsmith, William; McKinney, Walt; Frazer, David; Ma, Jane; Schwegler-Berry, Diane; Brain, Joseph; Castranova, Vincent
Abstract Nanoscale CeO2 is increasingly used for industrial and commercial applications, including catalysis, UV-shielding and as an additive in various nanocomposites. Because of its increasing potential for consumer and occupational exposures, a comprehensive toxicological characterisation of this nanomaterial is needed. Preliminary results from intratracheal instillation studies in rats point to cytotoxicity and inflammation, though these studies may not accurately use realistic nanoscale exposure profiles. By contrast, published in vitro cellular studies have reported limited toxicological outcomes for the case of nano-ceria. Here, the authors present an integrative study evaluating the toxicity of nanoscale CeO2 both in vitro, using the A549 lung epithelial cell line, and in vivo using an intact rat model. Realistic nano-ceria exposure atmospheres were generated using the Harvard Versatile Engineered Nanomaterial Generation System (VENGES), and rats were exposed via inhalation. Finally, the use of a nanothin amorphous SiO2 encapsulation coating as a means of mitigating CeO2 toxicity was assessed. Results from the inhalation experiments show lung injury and inflammation with increased PMN and LDH levels in the bronchoalveolar lavage fluid of the CeO2-exposed rats. Moreover, exposure to SiO2-coated CeO2 did not induce any pulmonary toxicity to the animals, representing clear evidence for the safe by design SiO2-encapsualtion concept.